Racial Discrimination in Health Care Is Associated with Worse Glycemic Control among Black Men but Not Black Women with Type 2 Diabetes - Shervin Assari; Shervin Assari; Daniel B. Lee; Daniel B. Lee; Emily Joy Nicklett; Maryam Moghani Lankarani; John D. Piette; John D. Piette; John D. Piette; James E. Aikens (Frontiers Media S.A., 2017)
BackgroundA growing body of research suggests that racial discrimination may affect the health of Black men and Black women differently.AimsThis study examined Black patients with diabetes mellitus (DM) in order to test gender differences in (1) levels of perceived racial discrimination in health care and (2) how perceived discrimination relates to glycemic control.MethodsA total of 163 Black patients with type 2 DM (78 women and 85 men) provided data on demographics (age and gender), socioeconomic status, perceived racial discrimination in health care, self-rated health, and hemoglobin A1c (HbA1c). Data were analyzed using linear regression.ResultsBlack men reported more racial discrimination in health care than Black women. Although racial discrimination in health care was not significantly associated with HbA1c in the pooled sample (b = 0.20, 95% CI = −0.41 −0.80), gender-stratified analysis indicated an association between perceived discrimination and higher HbA1c levels for Black men (b = 0.86, 95% confidence intervals (CI) = 0.01-1.73) but not Black women (b = −0.31, 95% CI = −1.17 to −0.54).ConclusionPerceived racial discrimination in diabetes care may be more salient for glycemic control of Black men than Black women. Scholars and clinicians should take gender into account when considering the impacts of race-related discrimination experiences on health outcomes. Policies should reduce racial discrimination in the health care.